Medical-Legal Aspects of Confidentiality in the Field of Pharmaceutical Health Care - Mujovic, Hajrija (LeXonomica, 2017)
The field of pharmaceutical health care is becoming increasingly established. Modernly, pharmacists learn more from patients about their prescriptions and other very personal, sensitive information. However, having access to an ever-increasing amount of sensitive, personal information raises serious issues pertaining to patient secrets and confidentiality. The term professional secrecy (hereinafter confidentiality) as well as any other form of discretion connected with a professional activity is construed broadly. However, the precise scope of confidentiality is not strictly defined in legislation. Obligation of professional secrecy has been diminished partly due to the general progress in a society and the progress of medical professions. The development of the protection of human rights is a continuous process.